Microbial profiles of Greek PDO cheeses assessed with amplicon metabarcoding. (October 2021) - Michailidou, Sofia; Pavlou, Eleftherios; Pasentsis, Konstantinos; Rhoades, Jonathan; Likotrafiti, Eleni; Argiriou, Anagnostis
Abstract: Greece is a country possessing many cheese products granted with a PDO (Protected Designation of Origin) certificate, with high exporting activities. In this study, we analyzed six popular cheese PDO products purchased from different industries to assess their microbial communities using amplicon metabarcoding analysis. To this end, using Next Generation Sequencing technology, we sequenced the 16S rRNA gene and the ITS spacer for prokaryotes and fungi, respectively. Alpha diversity indices revealed higher bacterial species richness for some cheeses (Kopanisti, Batzos) and poor for others (Feta, Galotiri). Kopanisti, together with Kalathaki and Anevato, also presented increased species diversity concerning fungal populations. Results showed that lactic acid bacteria (LAB) prevailed the bacterial populations in all samples ( Lactococcus, Lactobacillus, Streptococcus, Leuconostoc ), whereas for fungi, members of the Saccharomycetaceae, Dipodascaceae and Debaryomycetaceae families prevailed the fungal populations. Several other genera were identified that make up each product's microbiome leading to the creation of the unique organoleptic attributes of Greek PDO cheeses. However, the identified species could not be directly linked to certain cheese types, assuming that starter and adjunct cultures, combined with the raw material used during production greatly impact the microbial communities in cheeses. Our data, produced for the first time for six Greek PDO cheeses, can be exploited in the process of creating a core microbial signature within each cheese type, supporting the Greek brand name and valorizing cheese products. Highlights: Microbial analysis of six different Greek PDO cheeses (16S rRNA gene and ITS region). Assessment of microbiota using amplicon metabarcoding approach. Lactococcus, Lactobacillus, Streptococcus, Leuconostoc prevailed bacterial populations. Debaryomyces, Kluyveromyces and Kazachstania were the dominant fungi.